SOFTWARE IN MORPHOMETRY FOR DETERMINING THE BREED AFFILIATION OF HONEY BEES - Krupskiy, O. B.; Shkryl, A. A.; Torekhanov, A. A.; Uxikbayev, M. M. (ЗКАТУ им. Жангир хана, 2023)
In modern beekeeping, an important role is played by the use of technologies that help to manage the processes of selection and breeding work on bee families as efficiently and accurately as possible. One of these tools was morphometric analysis, a method used to study the shape, structure and size of various parts of the body of bees. Morphometric analysis provides valuable information about many aspects of bee life. It allows beekeepers to assess the health status of bees, their reproductive capabilities, as well as to detect possible pathologies or deviations. Thus, morphometric analysis is a key element in ensuring the productivity and health of bee colonies. Modern technologies greatly simplify and accelerate the process of morphometric analysis. There are many software solutions on the market designed specifically for morphometric analysis in beekeeping. They offer a variety of functionality, including automated measurements, data visualization, statistical processing, and more. The article combines an overview on the issue of software for conducting morphometry of honey bees and recommendations on the choice and use of this software. The software for classical and geometric morphometry was systematized and analyzed according to their functional capabilities.
Krupskiy, O. B. SOFTWARE IN MORPHOMETRY FOR DETERMINING THE BREED AFFILIATION OF HONEY BEES / O. B. Krupskiy, A. A. Shkryl, A. A. Torekhanov, M. M. Uxikbayev. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2023. - № 3-2 (72). Ч. ІІ. - Р. 203-214. - ISSN 2305-9397
Keywords: bees; beekeeping; morphometry; geometric morphometry; software; зкату; научный журнал